Phytochemicals Determination, and Antioxidant, Antimicrobial, Anti-Inflammatory and Anticancer Activities of Blackberry Fruits - Lidia Gil-Martínez; Nuria Mut-Salud; José Antonio Ruiz-García; Ana Falcón-Piñeiro; Mònica Maijó-Ferré; Alberto Baños; José Manuel De la Torre-Ramírez; Enrique Guillamón; Vito Verardo; Ana María Gómez-Caravaca (Foods, 2023)
A comprehensive characterization of the phytochemicals present in a blackberry fruit extract by HPLC-TOF-MS has been carried out. The main compounds in the extract were ursane-type terpenoids which, along with phenolic compounds, may be responsible for the bioactivity of the extract. In vitro antioxidant capacity was assessed through Folin–Ciocalteu (31.05 ± 4.9 mg GAE/g d.w.), FRAP (637.8 ± 3.2 μmol Fe2+/g d.w.), DPPH (IC50 97.1 ± 2.4 μg d.w./mL) and TEAC (576.6 ± 8.3 μmol TE/g d.w.) assays. Furthermore, the extract exerted remarkable effects on in vitro cellular antioxidant activity in HUVEC cells at a concentration of 5 mg/mL. Antimicrobial activity of the extract was also tested. Most sensible microorganisms were Gram-positive bacteria, such as E. faecalis, B. cereus and Gram-negative E. coli (MBC of 12.5 mg/mL). IC50 values against colon tumoral cells HT-29 (4.9 ± 0.2 mg/mL), T-84 (5.9 ± 0.3 mg/mL) and SW-837 (5.9 ± 0.2 mg/mL) were also obtained. Furthermore, blackberry extract demonstrated anti-inflammatory activity inhibiting the secretion of pro-inflammatory IL-8 cytokines in two cellular models (HT-29 and T-84) in a concentration-dependent manner. These results support that blackberry fruits are an interesting source of bioactive compounds that may be useful in the prevention and treatment of different diseases, mainly related to oxidative stress.